2014
DOI: 10.1021/ci500299h
|View full text |Cite
|
Sign up to set email alerts
|

Docking Ligands into Flexible and Solvated Macromolecules. 7. Impact of Protein Flexibility and Water Molecules on Docking-Based Virtual Screening Accuracy

Abstract: The use of predictive computational methods in the drug discovery process is in a state of continual growth. Over the last two decades, an increasingly large number of docking tools have been developed to identify hits or optimize lead molecules through in-silico screening of chemical libraries to proteins. In recent years, the focus has been on implementing protein flexibility and water molecules. Our efforts led to the development of Fitted first reported in 2007 and further developed since then. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 71 publications
3
38
0
Order By: Relevance
“…Therrien et al reported that when screened compounds are similar one to each other, and they bind the same active site form, adopting a multiple receptor conformation (MRC) approach ameliorates the ranking of decoys. A much more significant improvement can be achieved when ligands are structurally different and/or are accommodated by diverse binding site conformations ( Figure 2) [24]. This is in line with what had been shown several years ago in protein kinases, where crystal structures and modeled receptor-ligand complexes were selected for MRC docking based on the chemical diversity of their bound ligands [62,63,66].…”
Section: Choosing the Right Receptor Conformation In Virtual Screeningsupporting
confidence: 76%
See 2 more Smart Citations
“…Therrien et al reported that when screened compounds are similar one to each other, and they bind the same active site form, adopting a multiple receptor conformation (MRC) approach ameliorates the ranking of decoys. A much more significant improvement can be achieved when ligands are structurally different and/or are accommodated by diverse binding site conformations ( Figure 2) [24]. This is in line with what had been shown several years ago in protein kinases, where crystal structures and modeled receptor-ligand complexes were selected for MRC docking based on the chemical diversity of their bound ligands [62,63,66].…”
Section: Choosing the Right Receptor Conformation In Virtual Screeningsupporting
confidence: 76%
“…The "right' conformations should be able to provide the best results in terms of quantity and quality, where quantity corresponds to the percentage of active molecules identified in the early screening stage, and quality to the chemical diversity of these first ranked molecules. Both single-and multiple receptor conformation approaches [24] are significantly affected by the chosen binding site architecture, so that the key point is often represented by the capability of the conformational sampling to select the most representative states [145,190]. Some strategies were recently proposed to guide this conformational sampling.…”
Section: Choosing the Right Receptor Conformation In Virtual Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of excellent recent reviews have discussed the importance of incorporating structural flexibility to increase the success rate of CADD [100][101][102]. One of the most widely used methods to achieve this is MD simulation.…”
Section: Conformational Ensembles and MD Simulationsmentioning
confidence: 99%
“…Even so, backbone displacement should also be considered since it can strengthen the accuracy of side chain orientations (Bolia et al 2014). Existing methods that incorporate partial protein flexibility include Glide, RosettaLigand (Davis and Baker 2009), FLIPDock (Zhao and Sanner 2007), and FITTED (Corbeil et al 2007(Corbeil et al , 2008Corbeil and Moitessier 2009;Englebienne and Moitessier 2009a, b;Pottel et al 2014;Therrien et al 2014). Solvation also plays a crucial role in ligand binding stability by mediating the interaction between receptor and ligand.…”
Section: Flexibility and Solvent Effectsmentioning
confidence: 99%